A Comparative Review of ICMR, WHO, and EMA Guidelines for Good Clinical Laboratory Practices - Joshi, Rajat Kumar; Sarangi, Sudhir Chandra; Mohapatra, Sarita; Mallick, Saumyaranjan; Datta, Sudip Kumar (Journal of Laboratory Physicians, 2022)
With the advancement of clinical research and the increased burden on laboratory services, there is an unmet need for guidelines regarding proper laboratory functioning and reliable data generation. Several organizations from all over the world have published guidelines for these clinical and research laboratories. Good Clinical Laboratory Practices (GCLP) are stepwise procedures aimed at strengthening the quality of test results produced by all clinical laboratories engaged in human sample analysis. In this article, we attempt a comparison of the GCLP guidelines recently issued by the Indian Council of Medical Research with the guidelines released by the World Health Organization and the European Medicines Agency. Also, we have included and discussed several suggestions that, if included, will lead to the strengthening of the laboratory practices used for both research and patient care for overall improvement in the Indian healthcare system.
Keywords: clinical laboratory; Good Clinical Laboratory Practices; guidelines; healthcare system